2022
DOI: 10.1007/s43545-022-00490-w
|View full text |Cite
|
Sign up to set email alerts
|

Latent profiles of stigma and HIV pre-exposure prophylaxis among Black sexual minority men: an exploratory study

Abstract: Black sexual minority men (BSMM) are a priority population for HIV prevention efforts, including pre-exposure prophylaxis (PrEP) promotion. Intersectional stigma can be associated with deterrence from PrEP utilization among BSMM; this stigma has a novel context in the COVID-19 pandemic. To examine this, we investigated latent profiles of racial, sexuality-based, and related stigmas among HIV-negative BSMM in the COVID-19 pandemic and tested their association with PrEP use. We analyzed cross-sectional data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…11 Greater vaccine hesitancy among Black vs. White PWH and at-risk of HIV has been noted in other cohorts, despite this not being noted for Black vs. White people in the general population. 9,[12][13][14][15] The finding of higher vaccine hesitancy among Black PWH may reflect the disproportionate impact of intersectional stigma and discrimination (including race, gender, and HIV status) on health outcomes among Black PWH, in particular among Black women with HIV in our analysis, compounding experiences of distrust of public health authorities. 9,[12][13][14][15] Given that 72% of those with vaccine hesitancy wanted more to be known about the SARS-CoV-2 vaccine before receiving it, with Black vs. White PWH having greater mistrust of vaccine approval, it is possible that accelerated vaccine approval may have reinforced mistrust of public health authorities among racialized populations (i.e., because of knowledge of the Tuskegee Syphilis Experiment, discriminatory recruitment for studies, and disparities in medical services offered for conditions such as acute pain).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Greater vaccine hesitancy among Black vs. White PWH and at-risk of HIV has been noted in other cohorts, despite this not being noted for Black vs. White people in the general population. 9,[12][13][14][15] The finding of higher vaccine hesitancy among Black PWH may reflect the disproportionate impact of intersectional stigma and discrimination (including race, gender, and HIV status) on health outcomes among Black PWH, in particular among Black women with HIV in our analysis, compounding experiences of distrust of public health authorities. 9,[12][13][14][15] Given that 72% of those with vaccine hesitancy wanted more to be known about the SARS-CoV-2 vaccine before receiving it, with Black vs. White PWH having greater mistrust of vaccine approval, it is possible that accelerated vaccine approval may have reinforced mistrust of public health authorities among racialized populations (i.e., because of knowledge of the Tuskegee Syphilis Experiment, discriminatory recruitment for studies, and disparities in medical services offered for conditions such as acute pain).…”
Section: Discussionmentioning
confidence: 99%
“…9,[12][13][14][15] The finding of higher vaccine hesitancy among Black PWH may reflect the disproportionate impact of intersectional stigma and discrimination (including race, gender, and HIV status) on health outcomes among Black PWH, in particular among Black women with HIV in our analysis, compounding experiences of distrust of public health authorities. 9,[12][13][14][15] Given that 72% of those with vaccine hesitancy wanted more to be known about the SARS-CoV-2 vaccine before receiving it, with Black vs. White PWH having greater mistrust of vaccine approval, it is possible that accelerated vaccine approval may have reinforced mistrust of public health authorities among racialized populations (i.e., because of knowledge of the Tuskegee Syphilis Experiment, discriminatory recruitment for studies, and disparities in medical services offered for conditions such as acute pain). 16 Although concern regarding vaccine contents and mistrust of public health authorities were important factors driving vaccine hesitancy among Black PWH, care engagement was not associated with lower vaccine hesitancy among The proportion of people living with HIV in the study cohort who reported not having yet received the vaccine is graphed in blue over 7 two-month periods.…”
Section: Discussionmentioning
confidence: 99%